Teacher Burnout and Contextual and Compositional Elements of School Environment. (5th November 2019) - Shackleton, Nichola; Bonell, Chris; Jamal, Farah; Allen, Elizabeth; Mathiot, Anne; Elbourne, Diana; Viner, Russell
ABSTRACT: BACKGROUND: Teachers report higher levels of stress than most occupational groups. Burnout is a specific psychological condition that results from chronic job stress characterized by emotional exhaustion, low personal accomplishment, and depersonalization. This study considers associations between aspects of the school environment and teacher burnout. METHODS: Exploratory analysis of baseline data from a cluster randomized controlled trial of 40 schools and 2278 teachers in the United Kingdom. Multilevel methods were used to consider the associations between different compositional and contextual aspects of the school environment and teacher burnout. RESULTS: There was evidence for school effects on teacher burnout, evidenced by ICCs and likelihood ratio tests, supporting the association between school environment and teacher burnout. The factors most consistently associated with teacher burnout in our study were teachers' perceptions of the school's safety and support and student attitudes to learning. CONCLUSIONS: The school environment does influence teacher burnout. More research is needed to develop and test causal pathways between the school environment and teacher burnout, and to understand ecological and individual predictors of teacher burnout and the interaction between the two.